1995
DOI: 10.1111/j.1469-8749.1995.tb11953.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Upright Postural Sway of Children

Abstract: SUMMARY From 1988 to 1992. 1188 children (576 boys and 612 girls) three to 11 years old were studied using the Stasio‐analyzer to clarify developmental change of upright postural sway. Developmental change in the contact surface area of the sole, the coefficient of variation for the contact surface area, total sway area, total sway path and position of the centre of gravity were analysed. The contact surface area increased markedly between the ages of three to five and of seven to nine years, and increased sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
1
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 4 publications
6
51
1
2
Order By: Relevance
“…However, there was no significant difference in the LNG of children between the ages of 5 and 6 years. Our results are consistent with those of previous studies which showed that the area of total sway decreased markedly at 3-5 years of age and then slowly after 6 years of age (Usui et al, 1995). Postural stability does not appear to take a linear progression in children from 4 to 6 years of age, while in the same age interval, body size (height and weight) increases more linearly.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, there was no significant difference in the LNG of children between the ages of 5 and 6 years. Our results are consistent with those of previous studies which showed that the area of total sway decreased markedly at 3-5 years of age and then slowly after 6 years of age (Usui et al, 1995). Postural stability does not appear to take a linear progression in children from 4 to 6 years of age, while in the same age interval, body size (height and weight) increases more linearly.…”
Section: Discussionsupporting
confidence: 83%
“…These previous studies, however, included only two to three children aged 3-5 years. Usui et al (1995) reported that total area of sway decreased markedly at 3-5 years of age and then slowly after age 6. Several investigators have also reported an age-dependent decrease in postural sway in children (Shambes, 1976;Zernicke et al, 1982;Foudriat et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have observed that young children sway more than older children and young adults (e.g., Figura, Cama, Capranica, Guidetti, & Pulejo, 1991;Portfors-Yeomans & Riach, 1995;Riach & Hayes, 1987;Riach & Starkes, 1994;Usui, Maekawa, & Hirasawa, 1995). Usui, Maekawa, and Hirasawa (1995), for example, studied 1,188 children aged 3-11 years during upright stance and observed that the center of pressure area became smaller with age.…”
Section: Introductionmentioning
confidence: 99%
“…The immaturity of plantar arch development in younger children, with the concomitant posterior location of the COP (Usui, Muekawa, & Hirasawa, 1995), could have reduced the posterior boundary of their stability limits, thus placing greater attentional demands on controlling body sway in the AP direction. In this study, there appeared to be a developmental trend in the location of the COP from a posterior position seen in younger children to a more anterior position that is observed in adults (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%